Synergy between Traditional and Introduced Sustainable Land Management Practices in Ethiopia (Global Journal of Human-Social Science, 2016)
The current development effort of Ethiopian government emphasizes on marketoriented commodity production through specialization and diversification of enterprises that are complementary to specialized commodities. This household based package formulation is natural resources conservation based approach. Farmers of Hararge have rich and ecologically sound traditional land husbandry practices/knowledge base. "Traditional tie-ridging" is practiced for in-situ moisture conservation and intensification of cropping systems at plot level. RW is contained in the farm plot. There are some similar experiences in Tigray but should be further exploited to expand and introduce cash crop/ agroforestry in the rugged and undulating areas of Tigray. There was also good integration of biological and physical SWC techniques. Enterprises should be diversified, integrated and market-oriented to improve the livelihood of farmers. Important knowledge gained from Hararge to fill gaps in Tigray & other drylands of Ethiopia comprises water harvesting (in-situ moisture/ water harvesting through tie-ridges), irrigation (crop diversification and intensification), zero grazing and integrated & intensive watershed management approach.
Keywords: water harvesting; eastern and northern ethiopia; dry land areas; sustainability